ANALISIS VARIABEL PENGEMBANGAN PELABUHAN LAUT (PELABUHAN PENUMPANG) SEBAGAI BANDAR UDARA PERAIRAN UNTUK OPERASIONAL PESAWAT APUNG (SEAPLANE) DI INDONESIA - Revo Rizki Aditiya; Bambang Triadmojo; Latif Budi Suparma (Pondasi, 2022)
The operation of water aerodrome for seaplane operations in Indonesia is regulated within the scope of the minimum operational specifications of water aerodromes for serving seaplane with a maximum limit of 30 seats. The regulation provides only for planning in the air side and aviation safety, while in practice it also deals with the planning and development of sea or maritime transport on port, security and safety at the sea. The purpose of this study is to identify variables for the development of port (passenger port) so that they can be used as water airports for seaplane operations with security and safety aspects of shipping and aviation activities. The research was conducted using a qualitative method with a descriptive approach through observation regulation documents and semistructure interviews to 10 speakers from the Ministry of Transportation Indonesia, water airport operators, and community leaders. Based on the analysis of data, this research produces important variables in the development of port (passenger port) as water aerodrome for seaplane operations in Indonesia,  (1) need for specific laws and regulations, (2) need for a water airport authority, (3) the purpose of development by considering the categorization of shipping or maritime and aviation aspects.